Comparative In Vitro Evaluation of the Effects of Ticarcillin and Carbenicillin upon Pseudomonas aeruginosa - Kalkani, E. (1976)
An in vitro comparison of the effects of ticarcillin and carbenicillin was performed upon 164 strains of Pseudomonas aeruginosa. The two drugs displayed nearly identical inhibitory activities: for each, about 82.5% of the strains were inhibited by doses of 256 μg/ml or less. A low bactericidal activity was also observed. Strains of P. aeruginosa that were highly resistant to carbenicillin were also resistant to ticarcillin.